Enseñar español en la actualidad: contribuciones didácticas - Elena Gamazo Carretero (Investigação, 2016)
This book is a collection of various articles on didactics, written by several international subject matter experts. They address the main questions related to the contents and the skills required for Teaching Spanish as a Second or Foreign Language. The publication is geared towards current or future teachers, professors and researchers in the field of Spanish language teaching, and it can be used as bibliographical material. Its international and collective character make this compilation special, as the contributing authors write from Spain, Portugal and Belgium, where they teach and carry out their research. The articles in this book possess a timeless quality as they tackle topics that have been studied in the past and that will still be studied in the future. Each author presents their research combining the practical and the theoretical aspects of the matter they focus on, which offers the reader a possibility to create a comprehensive view of the topic. This promotes the knowledge on specific issues, and presents the way in which theoretical knowledge can be put into practice.